A soy-based product fermented by Enterococcus faecium and Lactobacillus helveticus inhibits the development of murine breast adenocarcinoma - Kinouchi, Fernanda Lopes [UNESP]; Geraldo Maia, Danielle Cardoso [UNESP]; de Abreu Ribeiro, Livia Carolina [UNESP]; Polesi Placeres, Marisa Campos [UNESP]; Font de Valdez, Graciela; Luis Colombo, Lucas; Rossi, Elizeu Antonio [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Purpose: Soy and its fermented products are considered functional foods. The study objective was to assess three functional food - a non-fermented soy product (NFP), fermented soy product (FSP), fermented soy product enriched with isoflavones (FI) - in terms of their ability to reduce the development of adenocarcinoma in mice, as well their ability on modulating immune system.Methods: It was observed tumor volume and to verify correlations with the immune system it was measured levels of the cytokines IL-1 beta and TNF-alpha produced by macrophages as well as IFN-gamma produced by lymphocytes using ELISA test, and nitric oxide production by macrophages using Griess reagent.Results: All products showed immunological activity, but FSP showed the most effective tumor containment, resulting in smallest tumor volumes. Fl animals expressed larger amounts of nitric oxide and IL-1 beta and exhibited larger tumor sizes than FSP and NFP animals.Conclusions: The results suggested that the ingestion of FSP was most efficient in tumor containment, possibly due to a positive modulation of the immune system by when Enterococcus faecium and Lactobacillus helveticus are added to the soy product. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Soy; Isoflavones; Cytokine; Cancer; Immune system